Analisis Efisiensi Pemasaran Hasil Tangkapan Nelayan Ikan Teri di Desa Buajangka Kecamatan Bungku Selatan Kabupaten Morowali - Riani Ahmad; Hapsari, Indri; Rahmad Madjid (Agrisurya, 2024)
The marketing of the products of a business in obtaining maximum profits will depend on the pattern of marketing channels. A business with good productivity will fail if the marketing is not good. One aspect of marketing that needs to be considered in an effort to increase goods from producers to consumers is marketing efficiency. The purpose of this study is to determine the pattern of marketing channels for anchovy fishermen's catches in Buajangka Village, South Bungku District, Morowali Regency, and to find out the marketing efficiency of anchovy fishermen's catches in Buajangka Village, South Bungku District, Morowali Regency. This research is a type of qualitative descriptive research with a qualitative data analysis method in the form of exposure and also quantitative analysis in the form of calculations. To find out the pattern of Anchovy marketing channels and marketing margins, marketing channel analysis was used, while to find out the share of prices received by producers, fishernan's share analysis was used. Based on the results of the study, it can be seen that the pattern of anchovy marketing channels in Buajangka village, South Bungku District, Morowali Regency has three channels, namely, channel one: fishermen - retailers - consumers, channel two: fishermen - collectors - wholesalers, three channels: fishermen - collectors - wholesalers - consumers. Where channels one and two are said to be efficient and channel three is inefficient.